2016
DOI: 10.1038/ncomms12965
|View full text |Cite
|
Sign up to set email alerts
|

Modelling proteins’ hidden conformations to predict antibiotic resistance

Abstract: TEM β-lactamase confers bacteria with resistance to many antibiotics and rapidly evolves activity against new drugs. However, functional changes are not easily explained by differences in crystal structures. We employ Markov state models to identify hidden conformations and explore their role in determining TEM’s specificity. We integrate these models with existing drug-design tools to create a new technique, called Boltzmann docking, which better predicts TEM specificity by accounting for conformational heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
159
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(170 citation statements)
references
References 72 publications
5
159
1
Order By: Relevance
“…FPOP is capable of reporting on protein transient dynamics, including fast folding 42 and alteration in side-chain flexibility 43 . We also showed that FPOP reveals fast fluctuations occurring remotely upon ligand binding, which is undetectable by slower footprinting methods 24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FPOP is capable of reporting on protein transient dynamics, including fast folding 42 and alteration in side-chain flexibility 43 . We also showed that FPOP reveals fast fluctuations occurring remotely upon ligand binding, which is undetectable by slower footprinting methods 24 .…”
Section: Resultsmentioning
confidence: 99%
“…The more rapid approaches offer an opportunity to understand protein dynamics and minor structural fluctuations. 43 …”
Section: Resultsmentioning
confidence: 99%
“…We ran 28 simulations, each 1 μs in length, following a previously published protocol (Hart et al, 2016). Each of these simulations was initiated from chain A of PDB ID 4YPI.…”
Section: Star Methodsmentioning
confidence: 99%
“…a correlation between the increased cefotaxime-degrading ability of the variants and the increased rigidity of the V-loop of TEM in the designed variants [98].…”
Section: B-lactamasesmentioning
confidence: 99%
“…In particular, as global structural features appear to be conserved over large spans of evolutionary time [84], it is non-trivial to use simply structural comparisons to rationalize the origins of the large observed changes in activity. Bowman and coworkers have used Markov state models (MSMs) [96,97] in order to construct maps of the conformational ensembles adopted by variants of the modern TEM b-lactamase [98], in order to explore the extent to which the conformational diversity of this enzyme can play a role in modulating activity. These MSMs allowed for the identification of 'hidden' conformational states that appear to be functionally relevant in determining specificity but are not visible from static crystal structures.…”
Section: B-lactamasesmentioning
confidence: 99%